Improved photocatalytic behavior of Ag-WO3/BiVO4 nanocomposite towards the removal of eosin yellow (EY) under visible light - Pandey S.K.; Sarwan P.; Tiwary D.; Salman M. (My University, 2025)
The photocatalytic removal of organic pollutants from wastewater is recognized as an economically viable and environmentally friendly technique. In this study, we successfully synthesized an Ag-WO3/BiVO4 (ABvW) nanocomposite photocatalyst that demonstrates exceptional efficiency in the photocatalytic degradation of eosin yellow (EY) dye. The synthesized photocatalysts were comprehensively characterized using various techniques, including BT-XRD, FE-SEM, XPS, BET and UV-DRS, to confirm their structural and optical properties. The photocatalytic degradation of EY was conducted under LED light illumination, and our findings reveal that the ABvW nanocomposite exhibits superior photocatalytic performance, achieving nearly 94 % dye removal within 70 min with a high Quantum yield (QY) value. This performance is significantly higher than that of pure WO3, BiVO4, or Ag/WO3 samples individually. The enhanced photocatalytic activity of the ABvW nanocomposite is likely due to the effective suppression of charge recombination, increased specific surface area, and improved redox potential of the composite material, all of which contribute to the superior photocatalytic performance of the ABvW nanocomposite. © 2025 Elsevier Ltd